DAMPAK MATA KULIAH KEWIRAUSAHAAN TERHADAP MINAT MAHASISWA UNTUK BERWIRAUSAHA SETELAH LULUS KULIAH PADA PROGRAM STUDI MANAJEMEN FAKULTAS EKONOMI UNIVERSITAS PEKALONGAN - Dwi Susilo; Kartono Muhammad (LPPM Universitas Pekalongan, 2014)
The Impact of Entrepreneurship Course to The Students Interest as an Entrepreneur After Graduation Lecture in Management Program, Economic Faculty of Pekalongan University aims to determine whether entrepreneurship courses have an impact on student interest in entrepreneurship after graduation , the results of the study concluded that 85 % chose jobs as entrepreneurial as preferred occupation, after college , before and after taking entrepreneurship courses, 52 % of students said that they chose jobs as entrepreneurial as affected entrepreneurship courses and the remaining 48 % is not due to the effects of entrepreneurship courses because of other factors , Asymp value . Sig . ( 2 - tailed ) of 0.00 thus Ho Denied means that there are differences in the working interest before and seudah students taking entrepreneurship courses , it can be seen that the 53% who chose to work as a clerk after graduating from college and moving interest as an entrepreneur after a entrepreneurship courses .. The Keywords : Entrepreneurship Course. Interest, Enterprenuer.